KEDUDUKAN WANITA DI IRAN: MENGUNGKAP PANDANGAN ULAMA SY’IAH - M. Sadik (State Institute of Islamic Studies (IAIN) Palu, 2005)
In Iran, woman emancipation does not undergo fundamental change compared with that in other Islamic worlds. In Iran, woman are still in subordinate position. It is within this context that conservative theological thought of Shi’i ulamas (Islamic scholars), especially Khomeni gave a great contribution to the subordinating of status of woman in Iran. This article tries to discuss status of woman in Iran from Shi’i ulama’s perspective. Kata Kunci: Kedudukan wanita, ulama Syi’ah